Clipless Laparoscopic Cholecystectomy: An initial experience of 50 cases in Bangladesh - Saha, PK; Roy, Ratna Rani; Rahman, Mamunur; Khan, Emrul Hasan; Reza, Syed Masud; Rabbani, Md. Golam; Alom, Kazi Shafiqul (Journal of Science Foundation, 2016)
Background: Laparoscopic cholecystectomy (LC) is one of the most common general surgical procedure. Objective: The purpose of the present study was to observe the surgical outcomes of the patients after clipless laparoscopic cholecystectomy. Methodology: This case series were performed in the Department of Surgery at Shaheed Suhrawardy Medical College & Hospital, Dhaka from June 2014 to April 2015. After several modifications, the success of intracorporeal separate knotting of cystic artery and duct was observed with Vicryl and was successfully used separate ligation of cystic artery and duct (SLAD) with Vicryl 1/0 in symptomatic cholelithiasis patients. Result: A total number of 50 cases were undergone elective laparoscopic cholecystectomy. Most of the patients were female (80.0%). Average age of patients was 39 yr (15-65). There was no bile leak or other complications related to ligature. The time taken for tie varied from 2 to 4 minutes (average 3 min). There were 10(25.0%) acute calculus cholecystitis, including empyema, gangrenous cholecystitis. No patient had port infection. Conclusion: Clipless LC is a safe and effective method. Journal of Science Foundation, 2015;13(1):11-14 DOI: http://dx.doi.org/10.3329/jsf.v13i1.27828